Implementasi Peraturan Presiden Nomor 72 Tahun 2021 Dalam Menunjang Percepatan Penurunan Stunting melalui Program Bangga Kencana - Kurniawan, Bagus Ananda; Indrayana, Samuel (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
This research analyzes aspects of the implementation of Presidential Regulation no. 72/2021 concerning the Acceleration of Stunting Reduction has mandated the establishment of a National Strategy for the Acceleration of Stunting Reduction. the importance of strong cooperation and coordination between ministries, institutions and regional governments to implement the National Strategy in an effort to accelerate the reduction of stunting prevalence in Indonesia. The research method used by researchers in this research is a qualitative approach. East Java BKKBN coordinates with Cross Ministries and Population Control, Family Planning Services. Women's Empowerment and Child Protection in the East Java area. The steps taken by the East Java BKKBN are strategic and appropriate steps, to safeguard the accountability of the Bangga Kencana program and accelerate the reduction of stunting. The East Java BKKBN as an iron stock is a role model in inviting the public to take part in the Bangga Kencana Family Planning Program. The East Java BKKBN is able to influence the community through socialization of the Bangga Kencana KB program to participate in government programs and reduce stunting rates.